Iceland : Selected Issues Paper. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2012)
This selected issues paper on Iceland reports that since mid-2009, Iceland has undergone a heavily frontloaded fiscal consolidation program to bring government finances to a sustainable level. To maintain the adjustment gains achieved during the last 2 1\2 years, the authorities have started drafting a new organic budget law, which would codify recent reforms in the budget framework and introduce principles for fiscal policymaking. Iceland's economy is exposed to adverse shocks. The external outlook continues to pose challenges, as key trading partners face weak growth prospects.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet